Employer Branding Corporate Reputation and Job Application Intentions: Moderating Effects Of Social Media And Value Congruence - Engga Jalaludin; Eeng Ahman; Amir Machmud; Yana Setiawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine and analyse the direct effect of employer branding on corporate reputation and job application intentions, as well as the effect of corporate reputation on job application intentions. Furthermore, this study also examines and analyses the mediating effect of corporate reputation on the relationship between employer branding and job application intentions, and the moderating effects of social media and value congruence on the relationship between employer branding and job application intentions. This study employs a quantitative approach, utilising an online questionnaire for data collection. A total of 220 respondents were recruited from final-year students enrolled in business faculties at various universities in Jakarta, Banten and West Java. Purposive sampling was used for sample selection, and data analysis in this study was conducted using SEM-PLS. The results of the testing and data analysis indicate that employer branding has a positive and significant impact on corporate reputation and job application intentions. Similarly, corporate reputation was found to have a positive and significant impact on job application intentions. Furthermore, employer branding has a positive and significant impact on job application intentions via corporate reputation; finally, social media does not moderate the influence of employer branding on job application intentions, but value congruence was found to moderate the influence of employer branding on job application intentions.